How does fatty mouthfeel, saltiness or sweetness of diets contribute to dietary energy intake?. (1st December 2018) - Cox, David N.; Hendrie, Gilly A.; Lease, Haidee J.; Rebuli, Megan A.; Barnes, Mary
Abstract: As "taste" is a primary driver of food choice, the objective of this study was to understand how the sensory properties of diets relate to energy intake (EI). A database of 720 frequently consumed foods, described by a trained panel for basic tastes (sweetness, saltiness) and fatty mouthfeel, was systematically applied to all foods reportedly consumed in 24hr recalls as part of the 2011–2012 Australian National Nutrition and Physical Activity Survey (n = 12, 153 adults and children). Food groups were classified according to the Australian Guide to Healthy Eating, and their contribution to total nutrient and sensory intake estimated. There were significant positive correlations between the nutrient and sensory properties of diets, for example, for adults, EI and fatty mouthfeel r = 0.740; EI and saltiness r = 0.623 and EI and sweetness r = 0.517 (all p < 0.01). Core foods (e.g. fruits, vegetables, grains, dairy) can provide similar sensory stimulation whilst being of lower energy content than discretionary foods (e.g. confectionary, snacks). Regression models in adults, controlling for age, sex and BMI, revealed that fatty mouthfeel (β = 0.492), saltiness (β = 0.161) and sweetness (β = 0.138) were significant predictors of EI, explaining 56% variance (p < 0.01). Similar results were found for children. Fatty mouthfeel was the primary driver of energy intake but such sensory stimulation can be derived from core (e.g. dairy foods), rather than discretionary foods, at lower energy content.